Routledge international handbook of internet gambling - Williams, Robert J.; Wood, Robert T., 1972-; Parke, Jonathan (Taylor and Francis, 2012)
Internet gambling is a rapidly growing phenomenon, which has profound social, psychological, economic, political, and policy implications. Until recently, Internet gambling has been understudied by the research community, but now a growing body of literature is emerging, on all aspects of Internet gambling and its attendant implications. As jurisdictions around the world grapple to understand the best way to respond to Internet gambling from a commercial, regulatory, and social perspective, scholarly studies of Internet gambling are becoming an ever more crucial resource. The>